PROSEDUR PENGUJIAN SUBSTANTIF AKUN PENDAPATAN PT XYZ OLEH KANTOR AKUNTAN PUBLIK KADIM VERONIA DAN SYAHIRMAN - Alifia Nida Rinesa (2022)
Substantive testing is an audit procedure designed to detect missage material on a level of assersion. Reception is the amount that is acceptable in the form of monetary from the entry of economic activities or from the results of the economic activities that are the biggest accounts that can be manipulated on profit reports. Substantial trials are conducted against the criteria set in the audit program. The audit procedure itself is a procedure made by the auditor to help the audit process became more organized. The substantial trials were conducted by the Kadim Public Accountant Office, Veronica and Syahrman and Syahirman admissions initiated with audit-consuming planning, proceeding with audit-consuming data requesting data related to the company's public information and accounting information and materialization. Next performed a detailed income detail to check out if there was a mistake or not. The following process of analytic procedures, vouching to sales and arrangeing a paper work examination. After the whole substantial testing against the income account has been done then can be concluded that the income account is income on the PT. XYZ has been served with natural and accounted for by the terms that apply and there is no material misstages.